Osobennosti fiziceskoj podgotovlennosti tennisistov 6-8 let - Skorodumova, A. P.; Baranov, I. S.; Kuznetsova, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In this article authors consider a problem of studying physical fitness structure of 6-8 years old tennis players training at the stage of basic training. Feature of this article is that results of the conducted research - the major factors defining the physical fitness of 6-7-8 years old tennis players training at the stage of basic training are published for the first time. Also for the first time the revealed changes of the factors significance and indexes entering them in age aspect are given in article. Authors come to a conclusion that for tennis players of each age indicators are defined which can become a basis of physical fitness monitoring for the purpose of its carrying out more than two times a year that in turn will allow to bring correction in training process for the purpose of its optimization